2022
DOI: 10.1007/s11739-022-03034-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the characteristics, morbidity and mortality of COVID-19 between first and second/third wave in a hospital setting in Lombardy: a retrospective cohort study

Abstract: Coronavirus disease 2019 (COVID-19) represents a major health problem in terms of deaths and long-term sequelae. We conducted a retrospective cohort study at Montichiari Hospital (Brescia, Italy) to better understand the determinants of outcome in two different COVID-19 outbreaks. A total of 634 unvaccinated patients admitted from local emergency room to the Internal Medicine ward with a confirmed diagnosis of SARS-CoV-2 infection and a moderate-to-severe COVID-19 were included in the study. A group of 260 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
6
15
0
Order By: Relevance
“…A literature search was carried out to retrieve other studies conducted in Italy, which, like us, carried out mortality analysis for COVID-19 patients admitted to hospital during the first three pandemic waves, both to compare our results with theirs and to understand whether other research groups conducted the follow-up of patients after discharge and for how long. In general, we found that the mortality trends that we observed among waves was very similar compared to that described by many other Italian research groups [ 6 , 7 , 8 , 23 , 25 , 27 , 28 , 29 ], with the highest mortality rate in hospitalized patients recorded during the first wave of the pandemic followed by a gradual decrease during the subsequent peaks of infection. Almost all studies involved patients who had been admitted to hospitals in Northern Italy.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A literature search was carried out to retrieve other studies conducted in Italy, which, like us, carried out mortality analysis for COVID-19 patients admitted to hospital during the first three pandemic waves, both to compare our results with theirs and to understand whether other research groups conducted the follow-up of patients after discharge and for how long. In general, we found that the mortality trends that we observed among waves was very similar compared to that described by many other Italian research groups [ 6 , 7 , 8 , 23 , 25 , 27 , 28 , 29 ], with the highest mortality rate in hospitalized patients recorded during the first wave of the pandemic followed by a gradual decrease during the subsequent peaks of infection. Almost all studies involved patients who had been admitted to hospitals in Northern Italy.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, one study did not perform any follow-up of patients after discharge, but it only considered death events that occurred during hospitalization by reporting an in-hospital mortality rate equal to 24% for the first wave, and 11% for the second/third [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leidi and colleagues in this issue of Internal and Emergency Medicine [ 1 ] confirm that COVID-19 waves are different in term of patients’ morbidity and mortality. In their paper, inpatient mortality was significantly higher (more than double) during the first wave than in the subsequent waves (24.2% vs. 11%).…”
Section: Commentarymentioning
confidence: 99%
“…Three studies looking at COVID-19 in Lombardy in the first or second wave in an internal medicine setting have been published so far [ 14 16 ]. Overall, comparison among these studies is made difficult by the heterogeneous inclusion criteria and admission modalities, reflecting in different results, despite similar patient age ranges.…”
mentioning
confidence: 99%
“…Overall, comparison among these studies is made difficult by the heterogeneous inclusion criteria and admission modalities, reflecting in different results, despite similar patient age ranges. For example, according to Bandera et al [ 15 ], the number of comorbidities and specific diseases (i.e., cancer, chronic heart failure, dementia and diabetes) were related to in-hospital mortality, while Leidi et al [ 14 ] did not find any association between survival and specific diseases. In the study by Ughi et al [ 16 ], the hazard ratio for mortality markedly increased with increasing Charlson comorbidity index.…”
mentioning
confidence: 99%